Management of sugarbeet seedling disease complex by combination of fungicides - R.C. TRIPATHI, S.N. SRIVASTAVA and (Indian Phytopathology, 2002)
The effectiveness of five combinations (two fungitoxicants in each combination) of 4 compatible fungicides, PCNB (brassicol), TMTD (thiram), carboxin (vitavax) and carbendazim (bavistin) at the rate of 2.5 g/kg seed (mixed in equal proportion) incorporated in seed pellets of sugarbeet was evaluated against seedling disease complex caused by 4 soil borne pathogens, namely, Pythium aphunidermatum; Rhizoctonia solanl, R. bataticola and Sclerotium rolfsii Seed pelleted with all combinations of fungicides provided better protection to seedlings as against steeping of seeds in aqueous suspension of a combination of fungicides. Of various combinations used, a mixture of bavistin + thiram was most efficaceous in reducing seedling mortality as compared to other treatments.